2005
DOI: 10.1152/ajpheart.01061.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of AT1 receptor antagonism on vascular and circulating inflammatory mediators in SHR: role of NF-κB/IκB system

Abstract: We investigated the role of angiotensin II in vascular and circulating inflammatory markers in spontaneously hypertensive rats (SHR). IL-1beta, IL-6, and TNF-alpha aortic mRNA expression and plasma levels were measured in adult SHR untreated or treated with the angiotensin II receptor antagonist candesartan (2 mg.kg(-1).day(-1)) or antihypertensive triple therapy (TT; in mg.kg(-1).day(-1): 20 hydralazine + 7 type 1 hydrochlorothiazide + 0.15 reserpine) for 10 wk. Likewise, aortic expression of NF-kappaB p50 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
95
1
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 36 publications
6
95
1
6
Order By: Relevance
“…Further, AT1 antagonism decreased the secretion of MCP-1 from PBMCs and the level of CCR2 in PBMCs. Previous studies of animal models of hypertension have also shown AT1 antagonists alleviating the detrimental effects of Ang II on endothelial cells and reducing the level of inflammatory response in vessels (Cheng et al, 2005;Sanz-Rosa et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, AT1 antagonism decreased the secretion of MCP-1 from PBMCs and the level of CCR2 in PBMCs. Previous studies of animal models of hypertension have also shown AT1 antagonists alleviating the detrimental effects of Ang II on endothelial cells and reducing the level of inflammatory response in vessels (Cheng et al, 2005;Sanz-Rosa et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…MCP-1 acts as a central mediator of the inflammatory response in hypertensive vascular disease (Usui et al, 2000;Sanz-Rosa et al, 2005;Willemsen et al, 2007). In response to Ang II, monocytes increase MCP-1 secretion, which plays an essential role in increased inflammation in the vessel (Ni et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that upregulation of inflammatory mediators in hypertensive patients can be used to predict the development of hypertension. The inflammatory process in hypertensive patients is characterised by expression of cytokines (interleukin [IL]-6, IL-1, and tumour necrosis factor alpha [TNF-a]), monocyte chemoattractant protein-1 (MCP-1), intercellular adhesion molecule 1 (ICAM-1), vascular cell adhesion molecule 1 (VCAM-1), and the corresponding activation of nuclear factor-kB (NF-kB) [6][7][8]. T lymphocytes are also thought to play a critical role in the pathogenesis of hypertension and vascular remodelling [9].…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptional factor Foxp3, which is expressed in T lymphocytes (including T helper cells [Th1, Th2, Th17] and suppressor T cells [including regulatory T cells]), has been reported to be critical for the production of angiotensin II, which plays a key role in the progression of essential hypertension [9]. Other studies have shown that the anti-inflammatory effects of angiotensin II receptor blocker (ARB) may be involved in the ability of these agents to lower blood pressure (BP) [6,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…De fato, diversos estudos têm demonstrado que os níveis circulantes de moléculas inflamatórias, como citocinas, quimiocinas, HSP60 e 70, Ang II e proteína C reativa, encontram-se elevados em SHR e em pacientes hipertensos (39)(40)(41). Em alguns casos, a detecção dos níveis plasmáticos de proteína C reativa pode colaborar com o prognóstico da hipertensão em pacientes (42).…”
Section: Resposta Imune E Hipertensão Arterialunclassified